The European Union with(in) international organisations commitment, consistency and effects across time - Orsini, Amandine (Globalisation, Europe, multilateralism, 2016)
Consisting of a two part structure, this book is focussed in Part I on more general trends of the EU's long-term participation with(in) International Organisations (IOs) and in Part II on more precise case studies on labour standards, public services, flexicurity, human trafficking and security.